Protesi bi-compartimentali di ginocchio: trend di utilizzo e analisi della letteratura - Farneti, A.; Perrone, F.L.; Breccia, M.; Rossi, B. (Lo Scalpello - Journal, 2019)
BI-COMPARTMENTAL KNEE ARTHROPLASTY: TREND OF USE AND LITERATURE REVIEW Minimally invasive surgery in knee arthroplasty has been a challenge since the 1950s, when the first mono-compartmental knee prostheses were implanted. The challenge was to treat the different osteoarthritis areas of the knee independently, saving soft tissue and healthy bones. Theoretically, bicompartmental knee arthroplasty (BKA) provides more physiological knee movement and the feeling of a “natural knee” compared to total knee replacement (TKA). Several prosthetic designs have been used with controversial results in the literature: although some authors have shown good functional results using BKA, a greater number of failures and complications have been detected than with TKA. In fact, to date, BKA is not recommended as a routine procedure, owing to the heterogeneity of studies and the lack of long-term follow-up studies. The purpose of this article was to clarify the use of bicompartmental knee arthroplasty (BKA). We have carried out a systematic literature review that includes 2 meta-analyses, 2 randomised controlled trials, 5 prospective controlled trials and international arthroplasty registries.